Juguemos de manera autónoma en los circuitos - Reyes Sánchez, Jany (2019)
The work of professional sufficiency had the title: “Let's play autonomously in the circuits”, the design of the learning activity, the investigation of the theoretical support of the game, the psychomotricity and circuit and the pedagogical support have been elaborated based on references bibliographical, as well as in the application of the knowledge learned, during the years of my professional training and according to my work experience with children._x000D_ The competence developed in the present activity was: “It develops autonomously through its motor skills”; the capacity, includes the body; the performance, realize actions and games autonomously, things such as running, jumping, climbing, rolling, sliding, spinning, kicking and throwing balls, etc. expressing emotions exploring the possibilities of the body in relation with the space, the surface and the objects, regulating his strength, speed and with some control of his balance; and the required performance, perform actions and games autonomously, such as running, jumping, walking and making turns to demonstrate balance in the circuits. The purpose of this activity was: which the children run, jump, walk and take turns autonomously in the circuits._x000D_ The children must understand that psychomotor activities are important in the progress of learning, because it allows them to develop all their senses through the movement and manipulation of the material, also through these activities they learn colors, sizes and problem solving.